Political Motivations - CALLANDER, STEVEN (Review of Economic Studies, 2008)
Are politicians motivated by policy outcomes or by the perks of office? The answer to this question is central to understanding the behavior of office holders and the policies they produce. Despite the question’s importance, however, the existing literature is not well suited to provide an answer. To shed light on the issue of political motivations I exploit a basic fact: to hold office, one must first win election. By characterizing the types of candidates that succeed in elections, I am able to predict the types that hold office and the policies that are produced. Toward this end, I develop a simple model of two candidate electoral competition in which candidates may be either office or policy motivated. In a second departure from standard formulations, the model incorporates both campaign and post-election behavior of candidates. In this environment I find that office motivated candidates are favored in electoral competition, but that their advantage is limited by the electoral mechanism itself, and policy motivated candidates win a significant fraction of elections. More importantly, I show that the competitive interaction among candidates of different motivations affects the incentives of all candidates — both office and policy motivated — and that this competition affects policy outcomes.